Temporada de Chicas: escritoras, investigación y compromiso en el contexto del movimiento feminista contemporáneo - Julia de Ípola (Cuadernos LIRICO)
This article seeks to confront the figure of the writer-investigator in Selva Almada's Chicas muertas (2014) with that of the fictional writer in Fernanda Melchor's Temporada de huracanes (2017). These two works revolve around one or several feminicide, and their publishing success coincides with the rise of Latin American feminisms. The aim of the comparison is, on the one hand, to examine the extent to which the writer-investigator’s concerns around gender issues, made explicit in the case of non-fiction, appear obliquely or veiled in the fiction novel and, on the other, to distill from this the singularities of the poetics of a feminist writer-investigator.